Hawa Cupcakes / Annisa Nurul Hidayah Jerman ... [et. al] - Jerman, Annisa Nurul Hidayah; Keram, Nurul Syazwanie Afikah; Othman, Sakinah; Mahsar, Dayang Noor Halimah (2014)
Hawa Cupcakes is a new business that operated at Kota Samarahan, Sarawak. It is the first business being managed by the bumiputera. The names of the business come out from the idea by the partnership members. We choose Hawa as our company name because the meaning of the word “Hawa” is really noble and Hawa also presents the strong of the women itself. Besides that, the name is also simple and easy to remember.